Structural, Morphological, and Antibacterial Attributes of Graphene Oxide Prepared by Hummers’ and Brodie’s Methods - Vittorio Marsala; Yuriy Gerasymchuk; Maria Luisa Saladino; Emil Paluch; Magdalena Wawrzyńska; Vitalii Boiko; Xiang Li; Cristina Giordano; Dariusz Hreniak; Beata Sobieszczańska (Molecules)
Graphite oxidation to graphene oxide (GO) is carried out using methods developed by Brodie (GO-B) and Hummers (GO-H). However, a comparison of the antibacterial properties based on the physicochemical properties has not been performed. Therefore, this paper outlines a comparative analysis of GO-H and GO-B on antibacterial efficacy against Gram-positive and Gram-negative bacterial cultures and biofilms in an aqueous environment and discusses which of the properties of these GO nanomaterials have the most significant impact on the antibacterial activity of these materials. Synthesis of GO with Brodie’s and modified Hummers’ methods was followed by an evaluation of their structural, morphological, and physicochemical properties by Raman, FTIR, UV–vis spectroscopy, and X-ray diffraction (XRD). The GO-B surface appeared more oxidized than that of GO-H, which could be crucial for interactions with bacteria. According to our results, GO-B demonstrated notably superior anti-biofilm efficacy. Despite its higher production cost, GO-B exhibits more excellent capabilities in combating bacterial biofilms than GO-H.